Effect of intraoperative HES 6% 130/0.4 on the need for blood transfusion after major oncologic surgery: a propensity-matched analysis (Clinics, 2013)
OBJECTIVES: To evaluate the effect of the intraoperative use of hydroxyethyl starch on the need for blood products in the perioperative period of oncologic surgery. The secondary end-points included the need for other blood products, the clotting profile, the intensive care unit mortality and length of stay. METHODS: Retrospective observational analysis in a tertiary oncologic ICU in Brazil including 894 patients submitted to oncologic surgery for a two-year period from September 2007. Patients were grouped according to whether hydroxyethyl starch was used during surgery (hydroxyethyl starch and No-hydroxyethyl starch groups) and compared using a propensity score analysis. A total of 385 propensity-matched patients remained in the analysis (97 in the No-hydroxyethyl starch group and 288 in the hydroxyethyl starch group). RESULTS: A higher percentage of patients in the hydroxyethyl starch group required red blood cell transfusion during surgery (26% vs. 14%; p = 0.016) and in the first 24 hours after surgery (5% vs. 0%; p = 0.015) but not in the 24- to 48-hour period after the procedure. There was no difference regarding the transfusion of other blood products, intensive care unit mortality or length of stay. CONCLUSION: Hydroxyethyl starch use in the intraoperative period of major oncologic surgery is associated with an increase in red blood cell transfusions. There are no differences in the need for other blood products, intensive care unit length of stay or mortality.